METHODS OF APPLYING THE PROBLEMS OF NATIONAL EDUCATION AND EDUCATION IN THE WORKS OF THE KAZAKH INTELLIGENTSIA IN TEACHING HISTORY - Alpatina Gulder Beibitshilikkyzy (European Research Materials, 2024)
The Kazakh people have always placed special emphasis on child-rearing. Thinking about a child’s well-being from an early age and giving significant importance to their upbringing forms an educated and well-mannered generation. The Kazakh people’s particular attention to child-rearing has likely paved the way for the emergence of many talented individuals. In the current era of accelerated globalization, indeed, national principles related to child-rearing are somewhat weakening. The wisdom of Ahmet Baitursynov, who is regarded as the teacher of the nation, encapsulates this sentiment well: "If you raise a child as a hero, he will become a hero; if you raise a child as a slave, he will become a slave." Our ancestors placed great emphasis on the upbringing of the younger generation, considering them the future of the nation. By paying attention to child-rearing from an early age, the process of personal development accelerates. Therefore, our people instilled values such as diligence, resilience in the face of difficulties, protecting national honor, knowing one’s ancestry, respecting words, wit, and intelligence, preserving traditions, respecting elders, and showing care for the younger ones from a young age. Travelers and researchers who visited the Kazakh land showed great interest in the lifestyle and traditions of the Kazakh people and left significant notes in their research regarding child-rearing.